Building Knowledge in Literacy and Health - Hemming, Heather E. (Can J Public Health, 2006)
Health and literacy share an interesting relationship. The complexities of the relationship between literacy and health need to be recognized by policy-makers and practitioners to dispel myths, reduce stigma attached to low literacy, and empower disadvantaged groups. As we engage in building knowledge in the field, there is a need for multi-sectoral collaboration, both quantitative and qualitative information, and more effective ways to communicate with and educate people with low literacy. At the Second Canadian Conference on Literacy and Health, research reported indicates that in terms of what we know, the field has focussed on: linking literacy and health; examining intervention programs; exploring e-health and rural health; evaluating programs; and empowering people. In exploring what we need to know, researchers at the conference identified the need to understand: the extent of literacy sensitivity among health care providers in diverse settings; the impact of using plain language and readability formulas; the effectiveness of approaches to instructing literacy; and the incorporation of health content and health literacy goals into literacy instruction. Further, we need to create accessible ways of sharing knowledge in the field to build and strengthen existing multi-sector partnerships within and between communities. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405371 and is accessible for authorized users.